2019
DOI: 10.1080/00472778.2019.1659684
|View full text |Cite
|
Sign up to set email alerts
|

Why some third age individuals develop entrepreneurial intentions: Exploring the psychological effects of posterity

Abstract: This study attempts to enhance our understanding of why some third age individuals develop intentions towards entrepreneurship. Based on the Theory of Planned Behaviour and its three antecedents of entrepreneurial intentions, this study contributes to the literature on psychological drivers of entrepreneurship among the elderly. Our results among 204 French individuals between 45 and 65 years old show that posterity positively moderates the relationship between entrepreneurial attitudes and entrepreneurial int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…The general entrepreneurship literature includes much research on the intentions and motivations that precede entrepreneurial action (Carsrud and Brannback, 2011; Kautonen et al , 2015). Overall, empirical studies have shown various antecedents to motivations for entrepreneurship (Amit and Muller, 1995; Dawson and Henley, 2012; Maalaoui et al , 2020), most consistently including the desire to exploit an identified opportunity and to be one's own boss (e.g. Shane and Venkataraman, 2000; Verduijn et al , 2014).…”
Section: The Drivers Of Social Entrepreneurshipmentioning
confidence: 99%
See 1 more Smart Citation
“…The general entrepreneurship literature includes much research on the intentions and motivations that precede entrepreneurial action (Carsrud and Brannback, 2011; Kautonen et al , 2015). Overall, empirical studies have shown various antecedents to motivations for entrepreneurship (Amit and Muller, 1995; Dawson and Henley, 2012; Maalaoui et al , 2020), most consistently including the desire to exploit an identified opportunity and to be one's own boss (e.g. Shane and Venkataraman, 2000; Verduijn et al , 2014).…”
Section: The Drivers Of Social Entrepreneurshipmentioning
confidence: 99%
“…However, whereas the commercial entrepreneur has been the subject of much inspection of motivations and drivers, with many studies finding there are myriad and diverse influences (e.g. Carsrud and Brannback, 2011; Maalaoui et al , 2020), in the social entrepreneurship context there is little exploration beyond the assertion of it as altruism. The most common interpretation is that an individual perceives a socially or ideologically-informed opportunity, and thereafter acts like an entrepreneur to build a social enterprise, and at both the opportunity identification and social enterprise creation stages, social entrepreneurship is regarded as a largely agential process (Miller et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, as discussed above, the empirical evidence including a meta-analysis conclude that the opposite is true. Specifically, older entrepreneurs are more likely to succeed than younger entrepreneurs [37]. A central theme throughout this chapter is to challenge some assumptions that the general public, the media, academics and other stakeholders in the entrepreneurship ecosystem have about who is an entrepreneur, who seeks to be an entrepreneur out of necessity or opportunity seeking, and who should be served by entrepreneurship support organizations.…”
Section: Resultsmentioning
confidence: 99%
“…Age is considered a key antecedent influencing EIs (Kautonen et al, 2011;. Alongside shifting age identitites and associated perceptions of age and retirement, is the desire to leave something for posterity (Barnhart and Peňaloza, 2013;Beehr and Bennett, 2015;Schafer and Shippee, 2009), which may psychologically impact on older people developing EIs (Maalaoui et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%